2006
DOI: 10.1128/aem.02699-05
|View full text |Cite
|
Sign up to set email alerts
|

Production of Xylitol from d -Xylose by a Xylitol Dehydrogenase Gene-Disrupted Mutant of Candida tropicalis

Abstract: Xylitol dehydrogenase (XDH) is one of the key enzymes in D-xylose metabolism, catalyzing the oxidation of xylitol to D-xylulose. Two copies of the XYL2 gene encoding XDH in the diploid yeast Candida tropicalis were sequentially disrupted using the Ura-blasting method. The XYL2-disrupted mutant, BSXDH-3, did not grow on a minimal medium containing D-xylose as a sole carbon source. An enzyme assay experiment indicated that BSXDH-3 lost apparently all XDH activity. Xylitol production by BSXDH-3 was evaluated usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
56
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(64 citation statements)
references
References 29 publications
2
56
0
6
Order By: Relevance
“…A number of yeasts and molds can produce xylitol from xylose because they possess the enzyme xylose reductase. Candida guilliermondii [10], Candida tropicalis [14,16], Candida boidinii [31], Candida magnoliae [29], Debaryomyces hansenii [26], and Pichia stipitis [13] are some of the yeasts with xylitol production capability.…”
Section: Introductionmentioning
confidence: 99%
“…A number of yeasts and molds can produce xylitol from xylose because they possess the enzyme xylose reductase. Candida guilliermondii [10], Candida tropicalis [14,16], Candida boidinii [31], Candida magnoliae [29], Debaryomyces hansenii [26], and Pichia stipitis [13] are some of the yeasts with xylitol production capability.…”
Section: Introductionmentioning
confidence: 99%
“…The first constructed cassette was composed of 5 0 HisF1, glutamic acid (glu), uracil marker (URA3), glutamic acid (glu), GAPDH promoter (P GAPDH ), zwf, GAPDH terminator (T GAPDH ), and 3 0 HisR1. The cassette contained two DNA fragments 5 0 HisF1 and 3 0 HisR1 flanking the first target hisG region, and was transformed into C. tropicalis L10 by homologous recombination system using lithium acetate method [12]. A gnd expression cassette was constructed by similar procedure.…”
Section: Methodsmentioning
confidence: 99%
“…We screened various carbon sources for xylitol production by this mutant strain, termed BSXDH-3, and found that glycerol was the best co-substrate for cell maintenance and NADPH regeneration [12]. In micro-organisms, NADPH is produced mainly via the pentose phosphate pathway (PPP), as a co-factor of two enzymes: (1) glucose-6-phosphate…”
Section: Introductionmentioning
confidence: 99%
“…High substrate concentration is imperative for the production of xylitol in a cost-effective way for scale up process. Significant steps towards the strain improvement for xylitol-production have been assumed [8][9][10].…”
Section: Introductionmentioning
confidence: 99%